Evaluation of personal cooling systems and simulation of their effects on human subjects using basic and advanced virtual environments - Elson, John Craig (Kansas State University, 2016)
The research presents the investigation of personal cooling systems (PCS) and their effects on humans from a thermodynamic perspective. The original focus of this study was to determine the most appropriate PCS for dismounted U.S. Army soldiers in a desert environment. Soldiers were experiencing heat stress due to a combination of interrelated factors including: environmental variables, activity levels, and clothing/personal protective equipment (PPE), which contributed to the buildup of thermal energy in the body, resulting in heat stress. This is also a common problem in industry, recreation, and sports. A PCS can serve as a technological solution to mitigate the effects of heat stress when other solutions are not possible. Viable PCS were selected from the KSU PCS database, expanded to over 300 PCS in the course of this study. A cooling effectiveness score was developed incorporating the logistical burdens of a PCS. Fourteen different PCS configurations were tested according to ASTM F2370 on a sweating thermal manikin. Four top systems were chosen for ASTM F2300 human subject testing on 22 male and 2 female soldiers in simulated desert conditions: dry air temperature = 42.2 ºC, mean radiant temperature = 54.4 ºC, air velocity = 2.0 m/s, relative humidity = 20%. Subjects wore military body armor, helmets and battle dress uniforms walking on treadmills at a metabolic rate of approximately 375-400W. All the PCS conditions showed significant reductions in core temperature rise, heart rate, and total sweat produced compared to the baseline (p<0.05). The expected mean body temperature was higher in the human subjects than expected based on the cooling obtained from the sweating manikin test. Lowered sweat production was determined to be the likely cause, reducing the body’s natural heat dissipation. The ASHRAE two-node model and TAITherm commercial human thermal models were used to investigate this theory. A method to account for fabric saturation from dripping sweat was developed and is presented as part of a new model. This study highlights that the response of the human body is highly complex in high-activity, high-temperature environments. The modeling efforts show the PCS moved the body from uncompensable to compensable heat stress and the body also reduced sweating rates when the PCS was used. Most models assume constant sweating (or natural heat loss) thus the PCS sweat reduction is the likely cause of the higher than expected core temperatures, and is an important aspect when determining the purpose of a PCS.
Keywords: Personal cooling system; Heat stress; Human subject testing; Saturated clothing model; Human thermal model; Thermal manikin testing